Quimiotaxia de Campylobacter fetus por substâncias do útero bovino gestante - Dionei Joaquim Haas (2015)
Campylobacter fetus is a pathogen that colonizes the bovine genital tract and placenta, however, the mechanisms responsible for the tissue tropism of this microorganism are unknown. Several mechanisms are important for tissue affinity of Campylobacter spp., including chemotaxis. In this study, the chemotactic activity of organic acids, amino acids, carbohydrates and inorganic ion, common uterine mucous components, in concentrations from 0.005M to 1M, and hormones produced by the bovine placenta, in concentrations of 0.005 ng/mL to 500 ng/mL, was evaluated for two strains of C. fetus subsp. venerealis and four strains of C. fetus subsp. fetus. Meso-erythritol, 17-estradiol and bovine placental lactogen presented no chemotactic activity in the concentrations tested, while sodium deoxycholate was chemorepellent for all strains tested. L-fucose, iron ferrous sulfate, sodium fumarate, sodium pyruvate, sodium succinate, L-aspartate, L-glutamate and L-serine were chemoattractants for the evaluated C. fetus subsp. venerealis and C. fetus subsp. fetus strains. Progesterone was chemoattractant, in concentrations above 50 ng/mL, for two strains of C. fetus subsp. fetus. Thus, this study showed that chemical substances present in the bovine uterus and placenta attract C. fetus subsp. venerealis and C. fetus subsp. fetus and that two strains of C. fetus subsp. fetus were attracted by high concentrations of progesterone.